2018
DOI: 10.3390/agronomy8050077
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Callus Induction and Regeneration in Selected Indica Rice

Abstract: An efficient callus induction and in vitro regeneration were developed using plant growth regulators, carbon sources, and basal media for three selected Malaysian wetland rice varieties (MR220, MR220-CL2, and MR232) and one upland variety (Bario). Effect of plant growth regulator (PGR) was carried out using four different concentrations (1-4 mg/L) of 2,4-D (2, 4-dichlorophenoxyacetic acid), and NAA (1-naphthalene acetic acid) (2.5, 5.0, 7.5, and 10 mg/L) with optimized 2,4-D. Effects of carbon sources (maltose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 63 publications
3
51
0
2
Order By: Relevance
“…In previous study it were showed that the callus induction frequency were between 60% and 90% [22], in the present study the callus induction rate reached up to 72% that support the previous study. However, high callus induction and regeneration may differ in different media composition and varieties [4], [5]. In this study, whitish and globular calli were found in media containing maltose and sucrose treated media formed brownish calli.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In previous study it were showed that the callus induction frequency were between 60% and 90% [22], in the present study the callus induction rate reached up to 72% that support the previous study. However, high callus induction and regeneration may differ in different media composition and varieties [4], [5]. In this study, whitish and globular calli were found in media containing maltose and sucrose treated media formed brownish calli.…”
Section: Discussionmentioning
confidence: 50%
“…In this experiment we used four types of media composition. MS medium containing 30g/L sucrose (T1) [23]; 30g/L Maltose (T2) [5]; 30 g/L Sucrose, 0.5 g/L Proline and 0.5 g/L Glutamine (T3) [24] and 30 g/L Maltose, 0.3 g/L Casein hydrolysate, 0.6 g/L L-proline and 0.25 mg/L BAP (T4). The culture media were autoclaved at 1.16 kgcm-2 pressure and 1210 C temperature for 30 minutes.…”
Section: Callus Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observation using BA in combination with NAA promoting plant regeneration from somatic embryos in rice has been reported (Lee et al 1999(Lee et al , 2002Saha et al 2017). Mostafiz and Wagiran (2018) reported that the medium fortified with 2.0 mg L −1 BA and 0.25 mg L −1 NAA promotes shoot development in rice. The germination of somatic embryos is affected by the subculture of embryogenic callus.…”
Section: Development Of Embryogenic Calli For Plant Transformationmentioning
confidence: 99%
“…2,4-D is also used in tissue cultures to induce somatic embryogenesis of plant cells (Gaspar et al, 1996;Mostafiz and Wagiran, 2018). Plant growth regulators such as 2,4-D induce pineapple flowering by increasing the content of ethylene in the meristematic zone of the plant (Burg and Burg, 1966;Abeles, 1968;Grossmann, 2010), where the absorption of products is faster (Cunha, 2005).…”
mentioning
confidence: 99%